TRAUMA-INFORMED SYLLABUS DESIGN FOR PRE-SERVICE TEACHERS - Holovatenko, Tetiana (Continuing Professional Education: Theory and Practice, 2024)
There is a growing body of literature that recognises the influence of trauma on the learning process. The article analyses foreign approaches to the development of curricula based on a trauma-informed approach. The relevance of the study is driven by the need to institutionalise the training of future teachers based on a trauma-informed approach in response to the challenges faced by education in the process of recovery from the COVID-19 pandemic and in connection with the full-scale war in Ukraine. The article aims to outline foreign practices of implementing a trauma-informed approach at the level of curricula and present practical ways to implement such practices in curricula and syllabi design in Ukraine. The study is based on the qualitative methodology of comparative pedagogical research with the use of grounded theory. The empirical data of the study were obtained from the analysis of scientific databases and websites of higher education institutions where programmes are developed on the basis of a trauma-informed approach. The results of the study outline ways to implement the principles of the trauma-informed approach in the programme and present the first experience of implementing certain elements of the approach in the training programme for future teachers. Some of the ways of implementing trauma-informed principles to syllabi design are to employ a friendly tone in the welcome message to students; articulate detailed expectations regarding assignments and grading policy; survey students to learn about their preferred accommodations and triggering topics; outline expectations regarding course support, attendance, participation, camera policy, and accommodations in cases of force majeure; provide links to university policies concerning students; provide students with flexible deadlines, task completion options, and formative assessment. The prospect of the research is to analyse the experience of students who studied under the proposed programme, as well as within the trauma-informed educational environment created by it.